La gestión del mantenimiento productivo total como herramienta de mejoramiento en empresas del sector manufactura (2020)
The main objective of this undergraduate study is the bibliographic review on total productive maintenance management or TPM, as a tool for improvement in organizations in the manufacturing sector worldwide. The TPM is a method to achieve the elimination of the so-called big six team losses, and the organization is challenged to successfully undertake the implementation of the TPM. Given the importance of this tool in the industry, a review was made of the success factors and obstacles that arise during the planning, implementation and maintenance management process.